Lecturer and Students’ Perception Toward the English Teaching Methodology - Amin, Fatimah Hidayahni; Jefri, Riny; Nasta, Mardiayanah (Universitas Islam Ahmad Dahlan (UIAD), 2021)
This study describes the perception of lecturer and students toward the English teaching methodology. The implementation of English teaching methodology underlay in nine aspects, namely: the use of lecturer’s utterances, the lecturer’s attitude, classroom rules, learning material, teaching media, learning activity, classroom interaction, classroom management, and assessment. In this study, the lecturer was the facilitator of the subject of English for Hotel and Restaurant. The students were the fourth semester students of Business English program, Faculty of Languages and Literature, State University of Makassar. Data on lecturer and students’ perception were taken by distributing questionnaires and giving interview questions. The data analysis showed that the students’ perception was categorized Positive towards the implementation of their lecturer’s English teaching methodology. This means that the students had a view that their lecturer had designed and implemented her teaching very well. Whilst, the lecturer’s perception was categorized strongly positive. This indicates that the lecturer had assured that her teaching program could help and facilitate her students to study well.